2020
DOI: 10.1111/1471-0528.16210
|View full text |Cite
|
Sign up to set email alerts
|

SSRI use during pregnancy and risk for postpartum haemorrhage: a national register‐based cohort study in Sweden

Abstract: Objective Evaluate whether selective serotonin reuptake inhibitor (SSRI) use during pregnancy, as well as prior or current untreated psychiatric illness is associated with postpartum haemorrhage (PPH). Design National register‐based cohort study based on data from the Swedish Pregnancy Register. Setting Sweden, nationwide coverage. Population A total of 31 159 pregnant women with singleton deliveries after gestational week 22+0 between January 2013 and July 2017. Methods Pregnant women with self‐reported SSRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…What is a clinically relevant effect size is still a topic for debate. We would argue that an odds ratio of about 1.3 for having a postpartum bleeding of more than 1000 ml (a strictly pre‐defined outcome in our study) 2 is not minimal. When dealing with prevalent exposures such as depression with/without use of SSRIs (at 20%), the public health impact of relatively small effect sizes is considerable.…”
mentioning
confidence: 63%
“…What is a clinically relevant effect size is still a topic for debate. We would argue that an odds ratio of about 1.3 for having a postpartum bleeding of more than 1000 ml (a strictly pre‐defined outcome in our study) 2 is not minimal. When dealing with prevalent exposures such as depression with/without use of SSRIs (at 20%), the public health impact of relatively small effect sizes is considerable.…”
mentioning
confidence: 63%
“…Thus, the reported rhetorical conclusion of this study 1 that ‘its results prompt design and implementation of studies testing effectiveness of risk evaluation of using SSRIs and the psychiatric illness itself with regard to reducing PPH’ seems incongruous with its findings. Birth attendants do not become distracted by any formal ‘PPH‐risk‐stratifying‐matrix’.…”
mentioning
confidence: 76%
“…A further unnoticed crucial limitation of the current study 1 is the incomplete data, i.e. the actual blood loss (average and SD) has not been mentioned/analysed; despite the midwives recording it as a continuous variable and binary data (≤1000 ml, >1000 ml) in the register.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One systematic review suggested that the evidence remained inconclusive but, if present, the absolute risk is low. More recently, a national register‐based cohort study suggested an odds ratio of 1.09 (95%CI 1.04–1.14) for women with prior mental illness, and 1.34 (95%CI 1.24–1.44) for women with current mental illness, when compared with healthy unmedicated women with no psychiatric history [32].…”
Section: Psychotropic Medication and Electroconvulsive Therapy In Prementioning
confidence: 99%